Social support among rural community-dwelling older adults and its association with depression and quality of life / Tengku Amatullah Madeehah T. Mohd. - Tengku Amatullah Madeehah, T. Mohd (2019)
The ageing population has become a global phenomenon and is causing an increase in both the economic and healthcare burden in many countries worldwide. As people age, they become more dependent on the people around them. Lack of social support has been shown to be associated with increased mortality, poor physical and mental health, and poor quality of life. The overall aim of this study was to determine the association between structural social support and functional social support and two outcomes, namely depression and quality of life. This study consists of a systematic review and a crosssectional study. First, a systematic review was conducted to critically analyse the literature on the association between social support and depression in the context of Asia. Second, a cross-sectional study was conducted among 2324 community-dwelling older adults aged 60 years in Kuala Pilah district, Negeri Sembilan. The respondents for the cross-sectional study were recruited by multi-stage sampling and interviewed face-to-face using a structured questionnaire. Structural social support was measured using the Lubben Social Network Scale, functional social support using the Duke Social Support Index, depression using the Geriatric Depression Scale and quality of life was measured using the Short Form Heath Survey-12. The results of the systematic review showed that in 23 out of the 28 studies, higher social support was associated with reduced depression among community-dwelling older adults in Asia. The systematic review also highlighted the importance of the family as a source of support in reducing depressive symptoms in the older adults. The data gathered by the cross-sectional study was analysed using structural equation modelling (SEM). Activities of daily living were hypothesised to act as a iv mediator between social support components and the outcomes of depression and quality of life, while age and chronic disease were treated as the confounders. Confirmatory factor analysis showed that support from family was the main indicator for structural social support. Older adults felt that having a role, being included in social groups, and having a confidant among family and friends were indicative of functional social support. The results of the SEM showed that between the two components of social support, only functional social support was found to be significantly associated with depression (b = -0.07), and quality of life (physical component (b = 0.08), mental component (b = 0.30)). In addition, the SEM showed that structural social support was associated with functional social support (b = 0.05). Moreover, functional social support was also found to be significantly associated with both outcomes in both groups of older men and women. In conclusion, this study found that higher functional social support was associated with reduced depression and better quality of life. Older adults in Malaysia rely on family to provide for their social needs. Hence, social support should be optimised and be seen as an asset to the older adult as they age. Meanwhile, government policy and services must be geared towards assisting older adults who lack support from family to improve their quality of life.